The Age of Digital Entrepreneurship and Digital Information Processing for Entrepreneurs: Are the Entrepreneurs in the Rural, Limpopo Province, South Africa Ready for This Era? - Lethoko, Mankolo Xaverine (Acta Universitatis Danubius. Œconomica, 2024)
The digital divide between urban and rural areas persists as a major challenge in achieving inclusive and sustainable development in South Africa. In rural provinces like Limpopo in South Africa, communities face significant barriers in accessing and utilizing digital skills, hindering their entrepreneurial potential and limiting their ability to benefit from digital platforms that can enhance and sustain their businesses. The problem lies in the lack of digital literacy and infrastructure challenges that impede entrepreneurs and rural communities from effectively utilizing digital tools and participating in the digital economy. This is a conceptual paper based on Technology Acceptance Model (TAM) as its framework which advocates for usage of technology by entrepreneurs. In the realm of digital entrepreneurship, TAM plays a crucial role in understanding and fostering technology adoption by entrepreneurs (Venkatesh et al., 2012; Agarwal & Prasad, 2013). Recent studies highlight its relevance for digital entrepreneurs navigating a rapidly evolving technological landscape (Sussman & Siegal, 2017; Liang et al., 2017). As digital ventures rely heavily on user acceptance, integrating TAM into the entrepreneurial process becomes strategic. However, in South Africa, the access to Information Technology Infrastructure is always a problem and entrepreneurs end up conducting their business using traditional methods of advertising such as mouth to mouth and also traditional payment methods like usage of cash. This study recommends that entrepreneurs in Limpopo should adopt the usage of technology as soon as possible in order to grow and sustain their businesses.